Contemporary Issues in African Sciences and Science Education - Asabere-Ameyaw, Akwasi; Sefa Dei, George J; Raheem, Kolawole (BRILL, 2012)
In this careful articulation of science, the editors provide an intellectual marriage of Indigenous science and science education in the African context as a way of revising schooling and education. They define science broadly to include both the science of the natural/physical/biological and the 'science of the social'. It is noted that the current policy direction of African education continues to be a subject of intense intellectual discussion.